Attracting students to transportation engineering: Gender differences and implications of student perceptions of transportation engineering careers - Ivey, Stephanie; Golias, Mihalis; Palazolo, Paul; Edwards, Stephen; Thomas, Patrice (My University, 2012)
With a significant fraction of the nation’s transportation workforce nearing retirement age, it is essential to attract new talent to transportation fields and to retain that talent. In addition, it is also important to attract a diverse workforce, because women and minorities are still significantly underrepresented in transportation engineering and related fields. To address the nation’s transportation workforce needs, FHWA, the U.S. Department of Transportation, the Institute of Transportation Engineers, and other leading transportation organizations emphasize the importance of outreach activities in kindergarten through 12th grade. In particular, programs directed at middle and high school students are essential for increasing the pipeline of transportation students and professionals. One such program at the University of Memphis in Tennessee, Transportation Engineering Careers (TREC), is designed to increase high school students’ interest in transportation careers through a week-long, fast-paced, active learning environment. This paper first provides a review of relevant literature and then presents assessment findings from the first 2 years of the TREC program regarding gender differences and student perceptions of transportation engineering. Finally, lessons learned and implications for similar efforts are also presented.